Tantangan dan penguatan legal drafting di indonesia: suatu kajian literatur terintegrasi - Alamsyah, Risky; Firdaus, Muhammad Rizal; Maharani, Rifa Arum Tazkya (Maliki Interdisciplinary Journal, 2026)
Legal drafting plays an important role in ensuring the quality and consistency of regulations as part of the national legal system. A number of studies show that the regulatory drafting process in Indonesia still faces recurring problems such as overlapping regulations, inconsistent norms, weak academic drafting, and suboptimal harmonisation between agencies. This article is a literature study that aims to identify patterns of these issues, map the factors that influence the quality of legal drafting, and assess its relevance to the needs of regulation formation in the digital era. The results of the study show that the quality of legal drafting is influenced by four main aspects: the competence of the drafters, legislative methodology, institutional coordination capacity, and the use of technology. Although the government has taken various strengthening measures, such as training drafters, developing technical guidelines, and digitisation through SPBE and JDIH, their effectiveness remains limited because they have not addressed more fundamental structural problems. Obstacles in the form of gaps in human resource capacity, weak system integration, and the suboptimal use of empirical analysis in academic papers are still consistently found in the literature. Therefore, a more comprehensive and integrated strengthening approach is needed to ensure that legal drafting can produce regulations that are adaptive, responsive, and relevant to the demands of modern legal development.